Flavonoids from Manilkara hexandra and antimicrobial and antioxidant activities. (February 2022) - Baky, Mostafa H.; Kamal, Amel M.; Haggag, Eman G.; Elgindi, Mohamed R.
Abstract: Manilkara hexandra (Roxb.) Dubard (family Sapotaceae) is an edible fruit-producing tree widely distributed in western and central Indian states and cultivated in Egypt. M. hexandra is well known for its various nutritional and medicinal merits. Structure elucidation of the isolated compounds using 1D and 2D NMR along with MS revealed the identification of two new flavonoids, myricetin 3- O (3″- O -methyl) α -L-rhamnopyranoside (1 ), and 3- O -ethyl-dihydroquercetin (3- O -ethyltaxifolin) (8 ) from M. hexandra leaves and fruits, respectively. Additionally, 4 known flavonoids were identified from the leaves as β -4′-methoxy-myricetin-3- O-α -L-rhamnoside (2 ), 4′-methoxy-quercetin-3- O-α -L-rhamnoside (3), quercetin-3- O-α -L-rhamnoside (5 ), and myricetin-3- O-α- L-rhamnoside (6 ), together with 4 known compounds from fruit identified as gallic acid (7 ), myricetin (9 ), taxifolin (10 ) and quercetin (11 ) in addition to methyl gallate (4 ). The isolated new compounds were investigated for their in vitro antimicrobial activity against 4 fungal and 8 bacterial strains. Compounds 1 and 8 showed antifungal activity against 3 fungal strains, and potent antibacterial activity was observed against tested gram positive and gram negative bacteria with the highest inhibition effect against Pseudomonas aeruginosa with MIC 3.9 μg/mL. The antioxidant activity of M. hexandra leaves and fruits aqueous methanol extract and methanol soluble portion was evaluated using DPPH method revealing DPPH radical scavenging activity and the fruit methanol soluble portion (FMSP) was the most active with SC50  = 12.8 (μg/mL) nearly equal to that of ascorbic acid. Graphical abstract: Image 1 Highlights: Two novel flavonoids were identified from Manilkara hexandra Dubard leaves and fruits. Nine known phenolic compounds were found for the first time in M. hexandra. In vitro antimicrobial activity of the new compounds. In vitro DPPH radical scavenging activity of M. hexandra extracts.